Light from the East? Ninian Smart and the Christian-Buddhist Encounter - Barnes, L. Philip (Scottish journal of theology, 1987)
One of the most pressing tasks for the Christian theologian at the present time is the construction of a theology of the religions which can adequately account for the continuing diversity of religious belief and practice, and which offers a distinctively Christian approach to religious pluralism. In the last few decades this topic has increasingly commanded the attention of prominent writers (e.g. P. Tillich, W. Pannenberg, J. Moltmann). Not only has it become the subject of numerous monographs and articles, but it seems to have established itself as an indispensable theme within any comprehensive (systematic) presentation of the Christian Faith.